2018
DOI: 10.1177/0748730418757007
|View full text |Cite
|
Sign up to set email alerts
|

Daily Profiles of Light Exposure and Evening Use of Light-emitting Devices in Young Adults Complaining of a Delayed Sleep Schedule

Abstract: A number of factors can contribute to a delayed sleep schedule. An important factor could be a daily profile of light exposure favoring a later circadian phase. This study aimed to compare light exposure between 14 young adults complaining of a delayed sleep schedule and 14 matched controls and to identify possible associations between habitual light exposure and circadian phase. Exposure to white and blue light was recorded with ambulatory monitors for 7 consecutive days. Participants also noted their daily u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
2
28
0
2
Order By: Relevance
“…self-selected exposure to artificial sources of light) also play an important role in the aetiology of DSWPD. This is supported by studies demonstrating increased night-time light exposure in DSWPD patients (Auger et al 2011;Van der Maren et al 2018), as well as modelling results that show increased use of artificial light sources J Physiol 596.24 amplifies individual differences in circadian and sleep timing (Skeldon et al 2017;Swaminathan et al 2017). Therefore, it is likely that delayed timing in DSWPD is a result of both physiological and behavioural differences.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…self-selected exposure to artificial sources of light) also play an important role in the aetiology of DSWPD. This is supported by studies demonstrating increased night-time light exposure in DSWPD patients (Auger et al 2011;Van der Maren et al 2018), as well as modelling results that show increased use of artificial light sources J Physiol 596.24 amplifies individual differences in circadian and sleep timing (Skeldon et al 2017;Swaminathan et al 2017). Therefore, it is likely that delayed timing in DSWPD is a result of both physiological and behavioural differences.…”
Section: Discussionmentioning
confidence: 80%
“…; Van der Maren et al . ), as well as modelling results that show increased use of artificial light sources amplifies individual differences in circadian and sleep timing (Skeldon et al . ; Swaminathan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between chronotype and sleep phenotype is less well-understood. Eveningness is associated with delayed sleep onset, as measured by both objective and subjective methods (Yadav and Singh, 2014;Van der Maren et al, 2018;Moderie et al, 2019). Evening orientation has also been associated with shorter sleep duration on work days and poorer sleep quality (Roepke and Duffy, 2010;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the fourth and last part of a larger research project and more details on subjects' selection can be found in the previous publications. [25][26][27] Subjects' characteristics are summarized in Table 1.…”
Section: Participants and Methods Participantsmentioning
confidence: 99%